Dysregulation of Thyroid Hormone Equilibrium in Hyperthyroidism: A Prospective Case Control Study of T3, T4 and TSH Dynamics - Sajad, Samah (American Journal of Biomedicine and Pharmacy, 2026)
Hyperthyroidism is a neuroendocrine disorder with dysfunction of the hypothalamic–pituitary–thyroid axis and systemic metabolic acceleration. Although clinically relevant, regional biochemical profiling of thyroid hormone changes has not been well characterized. Objective: To characterize changes in serum concentrations of triiodothyronine (T3), thyroxin (T4), and thyroid-stimulating hormone (TSH) in hyperthyroid patients, and to assess its distribution according to age and sex. In a prospective case–control study from February 2022 to March 2023, a total of 100 subjects (50 hyperthyroid patients (15 men and 35 women) and 50 control sexactly matched forage and within therangeo f25–65years) were comprised. Serum T3, T4 and TSH levels were determined respectively by fluorescence immunoassay (iCHROMA™system). Statistical comparisons were made by one-way ANOVA (P < 0.05; P < 0.01). The hyperthyroid patients had high endocrine dysfunction with T3 and T4 levels significantly increased and TSH level significantly decreased in the hyperthyroid patients compared to controls (P ≤ 0.01). Peak prevalence was found in the 40–60-year age group, prompting stratified analysis and indicating age-related susceptibility. In addition, there was also a strong female predominance (64%) underscoring the contribution of biological sex in disease presentation. Such a massive hormonal disturbance indicates a strong inverse relation between an excess of thyroid hormone and the negative modulation of the pituitary by TSH. Here, we describe an identifiable biochemical pattern of hyperthyroidism characterized by increased peripheral thyroid hormone action and feedback suppression of TSH. The results offer regional specific support for demographic determinants of disease distribution and demonstrate the clinical benefit of combined hormone profiling for detection of the disease at an early stage and the possibility of ongoing disease monitoring. These findings help improve diagnostic practices and may also guide endocrine evaluation in specific at-risk groups.